Work and organisations in 2020: The future we want?. Issue 9 (5th August 2014) - Totterdill, Peter; Exton, Rosemary
Abstract : Purpose: – The report aims to make the case for workplace innovation in an increasingly volatile global environment and outlines the opportunities for the creative and rewarding work that it affords. Work and Organisations in 2020 argues that workplace innovation has a major impact on both the performance of the enterprise and on national economic competitiveness. It boosts productivity, quality and innovation, by making better use of workforce talent and has a profound effect on employees' learning and development, health, well-being, ageing and wider roles as citizens. Design/methodology/approach: – Keys issues include: the intrinsic value of work; sustainable workplaces; harmonising technological innovation and human potential; entrepreneurship and developing and utilising skills. Findings: – The paper considers challenges to sustainable and effective change, and key issues concerning the way forward including responsible globalisation, new roles for public policy, new roles for trade unions and employers' organisations, a new labour market perspective, listening to the voice of employees and realising the promise of employee ownership. Originality/value: – The report concludes that there is a way towards a more coherent UK approach to renewing the employment agenda in the UK: an agenda that has often been somewhat fragmented and lacking in a strategic focus capable of guiding the efforts of different actors. At the heart of these values is a commitment to sustainable improvement in economic performance and social well-being, and an explicit rejection of short-termism.